Adding value to business continuity management through external relations - Iradi, Daniel P. (Henry Stewart Talks, 2011)
External relations and external resources, Identifying existing relationships, Developing new external relations, Interactions between BCM and EM, Government agencies as external resources, PS-prep in the USA, Networking opportunities, Businesses as external agencies, Community recovery and business continuity, NGOs, CBOs and FBOs, Emergency and family preparedness, Accessing external resources